2014
DOI: 10.1074/jbc.m113.474049
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleolar Protein Myb-binding Protein 1A (MYBBP1A) Enhances p53 Tetramerization and Acetylation in Response to Nucleolar Disruption

Abstract: Background: Nucleolar disruption is involved in cellular stress response and is sufficient for p53 activation. p53 tetramerization is crucial to exert its activity. Results: The nucleolar protein MYBBP1A enhanced p53 tetramerization by directly interacting with p53. Conclusion: p53 tetramerization by MYBBP1A is indispensable for activating p53 under nucleolar stress. Significance: This is the first report to describe the possible mechanism underlying p53 tetramerization in cells under nucleolar stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…We pulled down RNA-protein complexes using streptavidin beads and identified PURPL -associated proteins by mass spectrometry (Table S3). MYBBP1A, a protein known to stabilize p53, was strongly enriched (Figures 5A–C) in the PURPL pulldowns (Ono et al, 2014, Kuroda et al, 2011, Kumazawa et al, 2015, Akaogi et al, 2013). MYBBP1A is a predominantly nucleolar protein that associates with RNA and directly binds to p53 in the nucleoplasm resulting in p53 activation and stabilization (Ono et al, 2014, Kuroda et al, 2011, Hochstatter et al, 2012, George et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We pulled down RNA-protein complexes using streptavidin beads and identified PURPL -associated proteins by mass spectrometry (Table S3). MYBBP1A, a protein known to stabilize p53, was strongly enriched (Figures 5A–C) in the PURPL pulldowns (Ono et al, 2014, Kuroda et al, 2011, Kumazawa et al, 2015, Akaogi et al, 2013). MYBBP1A is a predominantly nucleolar protein that associates with RNA and directly binds to p53 in the nucleoplasm resulting in p53 activation and stabilization (Ono et al, 2014, Kuroda et al, 2011, Hochstatter et al, 2012, George et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…We show that loss of PURPL results in elevated basal p53 levels and impaired cell growth in vitro and in vivo . PURPL regulates basal p53 levels by associating with MYBBP1A, a protein known to bind to and activate p53 (Ono et al, 2014, Kuroda et al, 2011, Kumazawa et al, 2015). Altogether, our study provides functional insights on PURPL , demonstrating a role of this lncRNA in suppressing basal p53 levels.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that MYBBP1A plays an important role in the acetylation and activation of p53 [2,[28][29][30][31][32]. Under stress conditions in the nucleolus, which are produced by the inhibition of the ribosome synthesis or by the absence of glucose, rRNA transcription is blocked, and the RNA content in the nucleolus is reduced.…”
Section: Mybbp1a and Epigenetic Regulationmentioning
confidence: 99%
“…Both MYBBP1A-p53 binding sites (aa 643-1150 and aa 1151-1328) are required to facilitate p53 tetramerization and acetylation, so that only full-length MYBBP1A is able to promote p53 activation. Finally, the tetramer of acetylated p53, still bound to p300, binds to the promoters of its target genes and induces the expression of genes related to apoptosis and/or cell cycle arrest [31].…”
Section: Mybbp1a and Epigenetic Regulationmentioning
confidence: 99%
“…The nucleolar protein Myb-binding protein 1α (MYBBP1A) is known for enhancing p53 tetramerization by directly interacting with p53 [11]. Recently, MYBBP1A was identified as a binding partner of PARIS (parkin-interacting substrate, ZNF746), which suppresses rRNA transcription and increased p53, a molecular marker of nucleolar stress, in the SN of conditional parkin KO mice and in sporadic PD patients [12].…”
Section: Introductionmentioning
confidence: 99%